The Transformation of Tasamuh Value in Gamelan Art - Rizal, Syaiful; Qiptiyah, Titin Mariatul; Arifin, Zainal (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The spread of Islam in Indonesia by Wali Sanga was not only done through preaching, but also through traditional arts, such as gamelan. Unfortunately, with the development of modernization, interest in gamelan art began to decline. In fact, besides functioning as a medium of entertainment, gamelan is also full of Islamic educational values, especially the value of tasamuh (tolerance). This research focuses on the Kyai Samudro Gamelan Team in Jember Regency and aims to reveal how this local culture acts as a medium for the transformation of Islamic values, especially tasamuh, in building a harmonious society. Using a descriptive qualitative approach, the results show that the transformation of tasamuh values occurs through various aspects, such as the training process, performances, clothing, and songs.